CSR Balanced Scorecard Systems and Business Performances: SMEs Case Study - Wong, Edward Sek Khin; Muhamad, Rusnah; Yeap, Lau Wee (The South East Asian Journal of Management, 2015)
This paper aims to examine the performance measurement using the CSR Balanced Scorecard system in SMEs firms in Malaysia. It investigates the relationships of the four perspectives of CSR Balanced Scorecard system toward performance measurement. The purpose of this paper is to investigate whether or not the improvement of the non-financial CSR measures will lead to the improvement of performance measures. To test these relationships, data were collected using the four perspectives approach introduced by Utting (2007). The finding indicates that the organizational business performance can be greatly increased by putting greater emphasis to CSR measures. The results also reveal that the increases of firms customer’s satisfaction is caused by the increase implementation of CSR measurement. At the end of the article, the implications of this study for SME industries and some suggestions are discussed for future studies.